PUBLIC PARTICIPATION FOR IMPLEMENTATION OF PNPM MANDIRI PARIWISATA IN KARANG DIMA VILLAGE LABUHAN BADAS SUBDISTRICT SUMBAWA REGENCY - Bintang Rizki Sakinah; Andry Agung Dewanto (Jurnal Ilmu Pemerintahan Widya Praja, 2017)
The implementation of PNPM Mandiri Pariwisata is a program that expected to reduce poverty through tourism by tourist growth philosophy that will affect economic growth and poverty reduction. This study aims to analyze community participation and the improvement of community participation strategy in the implementation of PNPM Mandiri Pariwisata in Karang Dima Village Labuan Badas District Sumbawa Regency. This study is a descriptive study with a qualitative approach. Where the key informants who serve as resource persons in this study were selected using purposive sampling technique. Based on the analysis of public participation in the implementation of PNPM Mandiri Pariwisata in Karang Dima Village Labuan Badas District Sumbawa Regency in general can be considered good, base on the Participation in Planning, community involvement has been seen since the beginning of the activities, and then in Participation in Implementation community directly involved to carry out activities that have been adjusted to the priorities and activities of the community, then Participation in Utilization since the beginning, the community involved as subjects of activities so they could felt the benefit of the activities directly, and the last Participation in Evaluation community involvement in terms of evaluating the activities carried out in stages ranging from monitoring, surveillance, until the evaluation. While the strategy of increasing public participation in the implementation of PNPM Mandiri Pariwisata in Karang Dima Village Labuan Badas District Sumbawa Regency done by Enabling steps through the pattern of community development based on community activities, potential, and uniqueness of the location and community involvement as a subject, then Empowering through the access opening and forge partnerships with key stakeholders, and the last Protecting through participation in festivals and fairs as well as the fulfilment of raw material and supporting equipment. Referring to the results of the discussion, the authors suggest that to maintain public participation in PNPM Mandiri Pariwisata needed figures through tourism community such as tourism awareness group (Pokdarwis), whereas in order to enhance community participation, the pattern of development activities conducted through community-based tourism (CBT) .Keywords: Public Participation, Community Development, PNPM Mandiri Pariwisata